The Role of Social Media in the Dissemination of Public Information - Allika Ayu Diah Pitaloka; Cindy Syahputri; Dea Ramadhani; Nabilla Putri Anggreani; Syakila Niswatul Khaira; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
Social media has become one of the main communication platforms in the digital era for delivering public information. This study aims to analyze the role of social media in the dissemination of public information, identify challenges, and formulate optimization strategies. This study uses a descriptive qualitative method with data analysis from ten previous studies. The results show that social media has great potential in reaching a wide audience, but its effectiveness is often constrained by limited human resources, infrastructure and public trust. To improve its role, a more focused communication strategy, interesting content management, and better utilization of technology are needed.